Perceptions of nurses working in mental health services regarding the recovery‐oriented care approach: Findings from Africa - K. M. Kealeboga; E. M. Manyedi; S. Moloko‐Phiri (Wiley, 2023)
Abstract Background The recovery‐oriented care approach in mental health is recognised as the vision for mental health. People with a diagnosis of mental illness value the support and the individualistic approach emphasised in the recovery‐oriented mental health care approach as they believe it facilitates their recovery. However, as a developing country, Botswana has a long way to go in availing mental health care resources to people with mental illness, let alone adopting new mental health approaches such as recovery. Aim The study aimed to explore the perceptions of nurses working in mental health care facilities of recovery‐oriented mental health care. Methods Four mental health facilities from Botswana consented to participate in the study. A descriptive qualitative approach was utilised to explore nurses' views on how they perceive recovery from mental illness. Thirty nurses participated in the focus group discussions across the four study sites. All participants consented to participate and to be recorded. Tesch's (in Qualitative enquiry and research design: Choosing among five approaches. 3th ed. SAGE, 2013:198) thematic analysis was used for this study. Results Three main themes were identified in participants' perceptions of recovery‐oriented care mental health: Recovery from mental illness is possible, the Meaning of recovery from mental illness and Factors facilitating recovery from mental illness. Public Contribution The study offers a perspective into how nurses perceive recovery‐oriented approaches from a developing country and add to the gap existing in recovery‐oriented mental health care approach from the African context.